2018
DOI: 10.11648/j.ajcem.20180605.13
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Huoxue Jiedu Jiangtang Formulation on Endoplasmic Reticulum Stress in Diabetic Atherosclerosis

Abstract: Objecive: To study the effects of Huoxue Jiedu Jiangtang formulation (HJJF) on endoplasmic reticulum stress (ERS) coupled inflammatory response From the molecular mechanism in diabetic vascular disease. Methods: Type 2 diabetes were established in male SD rats by feeding high lipid diet and injection of streptozotocin. after T2DM models established successfully, the rats were divided into model group, low-dose HJJF group (HJJF 1 ), high-dose HJJF group (HJJF 2 ), and Western medicine group (Gliquidone+Benazepr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…As a result, blood stasis, phlegm turbidity, heat toxin depose and hold-up in the veins, accumulate plaques (that is, atherosclerotic plaques) [3]. Previous animal studies have found that Huoxue Jiedu Jiangtang Recipe (HJJR) can inhibit endoplasmic reticulum stress (ERS) cell apoptosis bypass of c-JUN N terminal kinases (c-JNK), decrease inflammatory response, reduce aortic cell apoptosis, and play protective effect on arteries [4]. CCAAT Enhance-Binding Protein Homologous Protein (CHOP) is a specific transcription factor of ERS, and activated c-JNK can phosphorylate and modify CHOP, increase the apoptotic effect of each other by regulating the activity of CHOP [5].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, blood stasis, phlegm turbidity, heat toxin depose and hold-up in the veins, accumulate plaques (that is, atherosclerotic plaques) [3]. Previous animal studies have found that Huoxue Jiedu Jiangtang Recipe (HJJR) can inhibit endoplasmic reticulum stress (ERS) cell apoptosis bypass of c-JUN N terminal kinases (c-JNK), decrease inflammatory response, reduce aortic cell apoptosis, and play protective effect on arteries [4]. CCAAT Enhance-Binding Protein Homologous Protein (CHOP) is a specific transcription factor of ERS, and activated c-JNK can phosphorylate and modify CHOP, increase the apoptotic effect of each other by regulating the activity of CHOP [5].…”
Section: Introductionmentioning
confidence: 99%